Przełomowe znaczenie Floriana Znanieckiego dla humanistyki (słowo na otwarcie debaty o mojej książce Uroszczenia i transaktualność w humanistyce) - Witkowski, Lech (Chowanna, 2023)
At the beginning of this transcript of the online debate, the author thanks some initiators and participants of the preliminary meeting. Then he confesses that his own attitude towards the book on Znaniecki needs a continuation. Next he mentions the leading analytical ideas of his intellectual approach. He identifies some theoretical challenges associated with such disciplines as philosophy, sociology, pedagogy and social psychology. The author also recalls the basic strategic ideas contained in Znaniecki’s concepts. He suggests the development of radically innovative emphases in this classic achievement and their application. The author refers to his articles written after the book was published, treating this sequence as a paradoxical order of preparation for further, detailed studies.